Indexes of Suspicion of Typical Cow's Milk Protein-Induced Enterocolitis - Hwang, Jin-Bok; Lee, Sung Hyuk; Kang, Yu Na; Kim, Sang Pyo; Suh, Seong-Il; Kam, Sin (Journal of Korean medical science, 2007)
This study was performed to identify clinical factors that facilitate the diagnosis of typical cow's milk protein-induced enterocolitis (CMPIE). Data from 142 consecutive patients (aged 15 to 45 days, cow's milk formula- or cow's milk and breast milk mixed-fed) admitted due to vomiting and/or diarrhea were retrospectively analyzed. These 142 subjects were divided into three groups: the CMPIE, infection, and non-infection group. Each group was composed of 16 (11.3%), 102 (71.8%), and 24 (16.9%) patients, respectively. On admission, poor weight gain (p=0.003), hypoalbuminemia (p=0.035), peripheral leukocytosis (p=0.012), and metabolic acidosis (p=0.015) were found to be more significant in the CMPIE group than those in other two groups. In CMPIE, serum albumin levels decreased from 3.3+/-0.9 g/dL on admission to 2.6+/-0.3 g/dL during admission (p<0.05), and methemoglobinemia was observed in 3 patients (18.8%) (p=0.012). Multiple logistic regression analysis showed that the independent predictors of CMPIE versus the infection group were failure to gain weight (OR, 10.75 [95% CI, 1.53-66.12]) (p= 0.014) and hypoalbuminemia (OR, 9.53 [95% CI, 1.62-49.01]) (p=0.010). The early recognition of indexes of suspicion for CMPIE may be of help in the diagnosis and treatment of this disorder.